Effects of aging and menopause on pancreatic fat fraction in healthy women population: A strobe-compliant article. Issue 7 (February 2019) - Yang, Wenjuan; Xie, Yi; Song, Bin; Xia, Chunchao; Tang, Chengwei; Li, Jing
Abstract : Abstract: Pancreatic fat fraction has been shown to increase in many pathological situations. However, pancreatic fat fraction and its physiological changes in healthy women are still unclear. The aim of this study is to investigate the effect of aging and menopause on pancreatic fat fraction in healthy female population. This was a cross-sectional study. A phantom of fat–water mixtures was established. One hundred sixty-seven healthy women (20–70 years) were recruited. Fat fraction was quantified with double-echo chemical shift magnetic resonance imaging with T1 and T2* correction. The association between measured and actual fat fractions was determined with Pearson correlation. Linear regression analysis was used to establish the calibration curve. Fat fractions were analyzed via analysis of variance. A significant positive linear correlation was revealed between the measured and actual fat fractions on the phantom ( r 2 = 0.991, P < .001). There was no significant difference in fat fractions among caput, corpus, and cauda of the pancreas. Pancreatic fat fraction remained constant during the age of 20 to 40 years (4.41 ± 0.79%) but significantly increased during the ages of 41 to 50 and 51 to 70 years (7.49 ± 1.10% and 9.43 ± 1.51%, respectively, P < .001). Moreover, pancreatic fat fractions of the healthy women aged 41 to 70 years were still significantly higher than these in the groups aged 20 to 40 years when postmenopausal healthy women were removed ( P < .001). For volunteers aged 46 to 49 years, pancreatic fat fraction of the postmenopausal women was significantly increased compared with that of their premenopausal counterparts ( P < .001). We found that an even distribution of pancreatic fat in healthy women, aging and menopause as 2 independent risk factors for pancreatic steatosis, a fatty infiltration in the pancreas beginning in the fifth decade in women.